2023
DOI: 10.1039/d2nj05554f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly dispersed Nb2O5–graphene heterojunction composites using ethylene diamine tetraacetic acid and boron-functionalized graphene quantum dots for symmetrical flexible supercapacitors with ultrahigh energy density

Abstract: Nb2O5 is a promising metal oxide electrode material for supercapacitors because of outstanding structural stability and wide electrochemical window, but low inherent conductivity hinders its many applications. The paper reports...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The CV curves exhibit different oxidation and reduction peaks in the measured potential window range corresponding to the redox nature of suNb 2 O 5 . [ 49,50 ] In addition, the CV current rises with increasing scan rate, demonstrating the fast diffusion of ions. CV graphs of the suNb 2 O 5 , CNS, and suNb 2 O 5 ‐CNS composite at a scan rate of 10 mV s −1 are shown in Figure 6h.…”
Section: Resultsmentioning
confidence: 99%
“…The CV curves exhibit different oxidation and reduction peaks in the measured potential window range corresponding to the redox nature of suNb 2 O 5 . [ 49,50 ] In addition, the CV current rises with increasing scan rate, demonstrating the fast diffusion of ions. CV graphs of the suNb 2 O 5 , CNS, and suNb 2 O 5 ‐CNS composite at a scan rate of 10 mV s −1 are shown in Figure 6h.…”
Section: Resultsmentioning
confidence: 99%
“…In another recent paper, Xiaoyue et al demonstrated a strategy for forming PN junctions and Schottky heterojunctions in a composite material using B-doped GQDs, which are electron-deficient elements. 155 In this study, B-GQDs acted as P-type semiconductors, creating PN junctions with Nb 2 O 5 /B-GQD and Schottky heterojunctions with Graphene/B-GQD, significantly improving the intrinsic conductivity of Nb 2 O 5 .…”
Section: Applications Of Gqdsmentioning
confidence: 93%
“…192 B-doping also induces hole formation in the graphene structure of GQDs, making them behave as p-type semiconductors. 155 B-doped GQDs (B-GQDs) can be synthesized by adding borax or boric acid (H 3 BO 3 ) as the B dopant to carbon sources such as glucose or 1,3,6-trinitropyrene (TNP) and subjecting them to hydrothermal treatment. Among the various B-C bonding structures present in B-GQDs, the graphite-like BC 3 structure plays a crucial role in enhancing the electrical conductivity of B-GQDs.…”
Section: Controlling Doping Of Gqdsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other key attributes of GQDs are that they are mostly water-soluble or dispersible, are generally biocompatible with human neural cells, have good photostability, and have low cytotoxicity. The photophysical properties of GQDs include but are not limited to nanosecond luminescence lifetimes and room temperature phosphorescence or white emission . GQDs are amenable to grafting onto other molecules, dyes, metal complexes, or polymers. , This rich chemistry of GQDs is exploited for the design and fabrication of nanodevices for electrocatalysis, electronics, light-emitting diodes, solar cells, , supercapacitors, and fuel cells. , They also have a high potential for biomedical applications involving diagnosis, drug delivery, gene delivery, bioimaging, and biosensing . Accordingly, this article focuses on the synthesis, modification, characterization, and biomedical applications of GQDs of size 20 nm or less …”
Section: Introductionmentioning
confidence: 99%